Kaempferol activates chloride secretion via the cAMP/PKA signaling pathway and expression of CFTR in T84 cells - Thaweewattanodom, Janjira; Deachapunya, Chatsri; Poonyachoti, Sutthasinee (Frontiers in Pharmacology, 2024)
Kaempferol is a flavonol identified as the most potent activator of chloride (Cl -) secretion among other flavonoids in airway epithelial cells. This study aimed to investigate the cellular mechanisms by which kaempferol stimulates Cl -secretion in the T84 human colon carcinoma cell line by Ussing chambers and voltage clamp technique. Bilateral addition of kaempferol (1-100 µM) increased shortcircuit current (Isc) in a concentration-dependent manner. Ion substitution of Cl -or CFTR inhibitors NPPB and glibenclamide or a Na + /K + /2Cl -cotransporter inhibitor bumetanide attenuated kaempferolinduced Isc response. In permeabilized monolayers, selective channel inhibitors CFTRinh-172 and CaCCinh-A01 inhibited kaempferol-induced apical Cl -current (ICl), and K + blockers BaCl2 and clotrimazole inhibited basolateral K + current (IKb). The kaempferol-induced ICl showed no additive effects with forskolin or 8cpt-cAMP. The kaempferol-induced ICl was mostly abolished by protein kinase A inhibitor H89, but not by tyrosine kinase inhibitors, AG490 and tyrphostin A23, or tyrosine phosphatase inhibitor vanadate. Treatment with kaempferol for 24 h increased the expression of CFTR protein as determined by the Western blot analysis. These results demonstrated that kaempferol activates Cl -secretion across T84 cells by activating the apical Cl -current and basolateral K + current. The mechanisms may involve the cAMP/PKA pathway and CFTR expression. Taken together, these findings reveal the beneficial effects of kaempferol to increase fluid secretion which can be used to treat constipation.